Coordinating English at Key Stage 1 - Tyrrell, Jenny (Subject leader's handbooks., 2000)
Provides advice and suggestions for improving practice, and shows a coodinator can create policies and links that work, exploit resources to the best effect, and develop the knowledge and expertise that will raise school standards.